2021
DOI: 10.3389/fpsyg.2020.581235
|View full text |Cite
|
Sign up to set email alerts
|

How Children Feel Matters: Teacher–Student Relationship as an Indirect Role Between Interpersonal Trust and Social Adjustment

Abstract: Previous studies have demonstrated positive correlations between children’s interpersonal trust and social adjustment. However, the psychological mechanism underlying this effect is still unclear. The current study tested the indirect roles of teacher–student relationships from both students’ and teachers’ perspectives in a Chinese context. In total, 709 pupils from grade three to grade five, and their 17 head teachers from a Chinese public primary school participated in this study. The Children’s Generalized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…Thus, developing emotional intelligence skills are a crucial factor in fostering flourishing in adolescents, especially if they have a poor relationship with their teachers. Previous studies have found that positive teacher-student relationship contributes greatly to adolescents' adjustment and well-being (e.g., Bakadorova and Raufelder, 2018;Lan and Moscardino, 2019;Borraccino et al, 2020;Dong et al, 2021). Our results expand on these findings by suggesting that, when the quality of the relationship with teachers is low, the association between emotional intelligence and flourishing become stronger.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Thus, developing emotional intelligence skills are a crucial factor in fostering flourishing in adolescents, especially if they have a poor relationship with their teachers. Previous studies have found that positive teacher-student relationship contributes greatly to adolescents' adjustment and well-being (e.g., Bakadorova and Raufelder, 2018;Lan and Moscardino, 2019;Borraccino et al, 2020;Dong et al, 2021). Our results expand on these findings by suggesting that, when the quality of the relationship with teachers is low, the association between emotional intelligence and flourishing become stronger.…”
Section: Discussionsupporting
confidence: 84%
“…The quality of the teacher-student relationship constitutes an important aspect in adolescents' development and mental health (Lippard et al, 2018;Wang et al, 2018Wang et al, , 2020. Previous studies have found that a positive and close teacher-student relationship may increase enjoyment in learning and social adjustment, leading to higher satisfaction of psychological needs and increased peer relationships at school, as well perhaps decreasing academic stress and school burnout in students (Bakadorova and Raufelder, 2018;Lan and Moscardino, 2019;Clem et al, 2020;Luo et al, 2020;Romano et al, 2020;Dong et al, 2021). Furthermore, some studies have shown the benefits of positive teacher-student relationship in promoting the development of adolescents' emotional intelligence (Wang et al, 2020) and buffering negative consequences of stressful situation (e.g., victimization) on psychological security (Jia et al, 2018).…”
Section: Teacher-student Relationship As Moderatormentioning
confidence: 99%
“…For example, several experimental studies examining the effect of teacher's emotional display on students' judgment of the teachers indicate that teacher's "hot" vs. "cold" display correlated with more positive ratings of the teacher, such as "more sociable" and "more humane" (Widmeyer and Loy, 1988;Mendzheritskaya and Hansen, 2019). Other learning-related outcomes, such as student-teacher relationships, teacher's popularity, and teacher's evaluation can be influenced by the connection of emotional display and perceptions of teacher's personality traits (Dong et al, 2021).…”
Section: Teacher's Emotional Display and Students' Perceptions Of Teacher's Personalitymentioning
confidence: 98%
“…Studies of teacher-student relationships quality usually assess the average students' experience in the classroom rather than teacher-student dyadic relationships quality, which may vary within dyads based on heterogeneity among students (Rucinski et al, 2018). If teacher-student relationships constitute a dyadic process by which interactions occur in a defined social context such as the classroom, then, obtaining insight knowledge regarding teachers' and students' perceptions on their interpersonal process could be valuable (Dong et al, 2021). Therefore, the examination of both parties' perceptions (teacher and students) needs to be considered simultaneously (Kenny, 2020).…”
Section: Introductionmentioning
confidence: 99%